Shielding our angels: Tackling workplace bullying against nurses working in community environments - Mohammed Ghalib Qutishat (Nursing Practice Today)
Background & Aim: Community health nursing plays a vital role in promoting health across diverse settings but faces challenges such as workplace bullying, which significantly impacts nurses' well-being and job satisfaction. Addressing these issues is essential to ensure safer working environments and improved care quality in Oman and globally. This study aims to examine the prevalence and experiences of workplace bullying against community nurses in Oman. Methods & Materials: This study utilized a descriptive cross-sectional design with convenience sampling, involving 197 community nurses who completed the questionnaires. That consists of demographics and the adopted form of the Experience of Bullying during Clinical Placement questionnaire, The survey was distributed via online link from September to October 2023. Results: The author distributed 230 questionnaires, and 197 participants replied, giving an 85.65 % response rate. Out of them, seventy-one percent experienced community-based bullying, primarily verbal (35.7%) and emotional (33.6%) abuse, mostly from Occupation/institution employees (33.6%). While 71.1% were aware of the reporting system, underreporting was common due to perceived inaction and unclear procedures (65%). Alarmingly, 71.1% intended to leave their jobs, underscoring the urgent need for stronger measures against workplace bullying among nurses in Oman. Conclusion: The research found that 71.1% of community nurses in Oman experience recurring workplace bullying driven by employment and social factors. Nurses face mistreatment and are dissatisfied with reporting and organizational responses. Alarmingly, 71.1% want to leave, risking healthcare quality. Comprehensive measures are needed to improve safety, reporting, training, and coordination to protect these frontline workers.